2008
DOI: 10.1590/s1414-81452008000300004
|View full text |Cite
|
Sign up to set email alerts
|

A prática de enfermagem no sistema penal: limites e possibilidades

Abstract: The nursing practice inside the penal system: limits and possibilities La práctica de enfermería en el sistema penal: límites y posibilidades Esc Anna Nery Rev Enferm 2008 set; 12 (3): 417-23 RESUMOJoanir Pereita Passos² Mônica Oliveira da Silva e Souza¹ O presente trabalho teve como objetivos identificar os princípios que norteiam a prática de enfermagem e discutir os limites e as possibilidades da atuação da equipe de enfermagem nos serviços de saúde do Sistema Penal do Estado do Rio de Janeiro. Para alcança… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 1 publication
0
8
0
10
Order By: Relevance
“…Regarding these aspects, while evidenced with satisfactory rates among professionals, the lack of freedom and autonomy for the performance of care are pointed as obstacles to health actions in the prison system, since the Prison Security Officer (ASP) is constantly present during the service and, also, there is an appreciation for safety-and discipline-related aspects to the detriment of health care 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding these aspects, while evidenced with satisfactory rates among professionals, the lack of freedom and autonomy for the performance of care are pointed as obstacles to health actions in the prison system, since the Prison Security Officer (ASP) is constantly present during the service and, also, there is an appreciation for safety-and discipline-related aspects to the detriment of health care 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The economic/political sphere, consisting of aspects of job security, financial resources, extra benefits and working hours was evaluated at a satisfactory level among health professionals. A survey conducted in the prison sector in the state of Rio de Janeiro with the nursing category has shown that most of these professionals had entered the prison system due to the stability related to the public examination 31 .…”
Section: Discussionmentioning
confidence: 99%
“…17 However, Diuana¹² clarifies that "often it is the prison guards who judge the need for care based on the prisoner's request and act to facilitate or hinder this access." Assuming that the conditions of life and health are important and have an affect on their behavior and their integration into society, it is known that confinement in prisons can by itself affects the stability of an individual; what happens then when the health care is permeated by scenarios of neglect and social exclusion?…”
Section: Discussionmentioning
confidence: 99%
“…No ambiente prisional, além da pouca habilidade dos profissionais relacionarem-se com seus pacientes, muitas vezes por medo e estigmas, existem dificuldades que prejudicam uma assistência adequada, como segurança, estrutura física/organizacional, gestão de pessoas e recursos materiais (19) . Com relação ao primeiro, o reconhecimento por parte dos internos de que a profissão é essencial para a manutenção da saúde dentro da unidade, tem minimizado a periculosidade do trabalho (20) , mas o segundo ainda precisa avançar.…”
Section: Enfermagem Família Drogadição E Encarceramentounclassified